Correlation of serum zinc and magnesium with reduced heart rate variability in male Parkinson’s disease patients - Nova, Naoreen Khan; Sultana, Shamima; Akther, Rubina; Habib, Md Ahsan (Journal of Bangladesh Society of Physiologist, 2024)
Background: Parkinson’s disease (PD) is a neurological disorder associated with altered cardiac autonomic function. Heart rate variability (HRV) analysis is a tool to assess the cardiac autonomic status. Altered serum zinc (Zn) and magnesium (Mg) levels are observed in PD. The serum Zn and Mg alteration is associated with nerve function impairment. Objective: To evaluate the relationship between serum zinc, magnesium, and time domain measures of HRV in male patients with PD. Methods: This observational analytical cross-sectional study was conducted in 2023on 30 newly diagnosed male PD patients aged 50-60 years. In this study, 30 healthy volunteers were the control. The 30 patients were divided into different categories based on serum mineral levels. The HRV was recorded by Power Lab 8/35, AD Instruments, Australia and the time domain measures of HRV were used in data analysis. The serum Zn and Mg levels were measured by atomic absorption spectrophotometry. Independent sample ‘t’ test and Pearson’s correlation coefficient test were used for statistical analysis and p<0.05 was considered statistical significance. Results: Significantly higher mean HR (Heart rate) (p<0.01) and significantly lower mean RR (Normal to normal QRS complex) interval,CVRR (Coefficient variation of RR interval) (p<0.01), SDRR (Standard deviation of the RR intervals), SDSD (Standard deviation of the difference between successive RR intervals), RMSSD (Square root of mean squared differences of successive RR intervals), pRR50% (Proportion of RR interval with duration >50 ms) (p<0.001)were observed in PD patients compared to control. In PD patients, significantly lower (p<0.001) serum Zn and significantly higher (p<0.01) serum Mg were observed compared to control. In addition,significant decrement was observed in SDRR, CVRR (p<0.05), SDSD, RMSSD, and pRR50% (p<0.01) in hypozincemic PD patients compared to normozincemic patients. On correlation analysis, significant positive correlations of serum Zn were observed with SDRR (p<0.05),SDSD (p<0.001), RMSSD (p<0.001) and pRR50% (p<0.01). Moreover,serum Mg was positively correlated with SDRR (p<0.05) in PD patients. Conclusion: Hypozincemia and magnesium were directly related to reduced HRV in male PD patients. J Bangladesh Soc Physiol 2023;18(2): 63-71